Antara Matematika, Teologi dan Kota - Adrianus Yosia (TRANSFORMATIO: Jurnal Teologi, Pendidikan, dan Misi Integral, 2024)
These days, urban expansion and its associated social and ecological challenges are unavoidable. The clever yet morally upright people who create changes in this circumstance are one of the answers. I argued that a K–12 education can aid in the formation of morally upright and competent individuals. My argument is that, in order for students to eventually transform the city, a theological foundation for mathematics instruction can help them improve their character and cognitive abilities. Because of this, a theological perspective on mathematics education can help students grow as individuals and advance society by enhancing their knowledge. In line with the assertion, I think that the definition of mathematics and theology, their shared goal, and the ways in which they might help students become more morally upright constitute the intersection of these two fields. Trust, direction, and articulation are the end results. Trust is an invitation to consider and devise solutions for ecological and social issues. Direction is an invitation to map out the answer based on completed reflection. Finally, articulation is the attempt to carry out a decision in light of reflection.